Republic of Niger Priorities for Ending Poverty and Boosting Shared Prosperity : Systematic Country Diagnostic - World Bank Group (World Bank, Washington, DC, 2017)
This document presents the systematic country diagnostic (SCD) for Niger. It identifies the constraints and opportunities for achieving the twin goals of ending poverty and improving shared prosperity by 2030 in a sustainable manner while acknowledging: (a) the need for selectivity, and (b) the need to identify constraints that can feasibly be addressed. The objectives of the World Bank are closely associated with those of the Government of Niger, which aims in its renaissance program, to achieve rapid poverty reduction by 2035. To put Niger on a sustainable path of poverty reduction, a change in trajectory is needed urgently. Though poverty reduced over the past decade, much of it can be attributed to favorable external conditions which no longer exist.